2018
DOI: 10.1016/j.cretres.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Dinocyst stratigraphy and palaeoenvironmental interpretation of the Cretaceous/Paleogene boundary at Stevns Klint, Denmark

Abstract: A re-examination of the uppermost Maastrichtian chalks and an expanded section of the Fish Clay (Fiskeler Member) undertaken at Stevns Klint, Denmark, one of the classic outcrops of the Cretaceous/Palaeogene boundary, has identified diverse and abundant dinoflagellate cyst assemblages, which are compared with earlier dinoflagellate cyst (dinocyst) studies. The uppermost part of the white coccolith chalk (Sigerslev Member) of the uppermost Maastrichtian is placed in the Palynodinium grallator Zone. The overlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In the Brazos River area, and in the Stevns Klint succession there is no evidence of a total productivity collapse (= Strangelove Ocean model), unless it was of such short duration as to be undetected. Dinocyst productivity appears to continue across the K/Pg boundary in a number of locations (Molina et al, 2006;Prauss, 2009;FitzPatrick et al, 2013FitzPatrick et al, , 2018Tuba Aydin, pers. comm., 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the Brazos River area, and in the Stevns Klint succession there is no evidence of a total productivity collapse (= Strangelove Ocean model), unless it was of such short duration as to be undetected. Dinocyst productivity appears to continue across the K/Pg boundary in a number of locations (Molina et al, 2006;Prauss, 2009;FitzPatrick et al, 2013FitzPatrick et al, , 2018Tuba Aydin, pers. comm., 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(Rasmussen et al, 2005) argued that the Fiskeler Member corresponds to the lowermost Paleocene planktic foraminiferal Zone P0. The dinoflagellate studies of (Brinkhuis et al, 1998) and (FitzPatrick et al, 2017) demonstrated that the Fiskeler Member is characterized by the first occurrences of the marker taxa Senoniasphaera inornata and Carpatella cf. cornuta, similar to the boundary clay layer of the K-Pg boundary GSSP at El Kef (Tunisia), comfirming the assignment of Zone P0 to the Fiskeler Member When the Fiskeler Member is considered as representing planktic foraminiferal Zone P0 of (Olsson et al, 1999), this biozone attains a thickness of around 27-28 cm at the Kulstirenden A outcrop of Stevns Klint.…”
Section: Age Modelmentioning
confidence: 99%